Localized Peptidoglycan Biosynthesis in Chlamydia trachomatis Conforms to the Polarized Division and Cell Size Reduction Developmental Models - Liechti, George W. (Frontiers in Microbiology, 2021)
Cell size regulation in bacteria is a function of two basic cellular processes: the expansion of the cell envelope and its constriction at spatially-defined points at what will eventually become the division plane. In most bacterial species both cell wall expansion and restriction are dependent on peptidoglycan (PG), a structural polymer comprised of sugars and amino acids that imparts strength and rigidity to bacterial membranes. Pathogenic Chlamydia species are unique in that their cell walls contain very little PG, which is restricted almost entirely to the apparent division plane of the microbe’s replicative forms. Very little is known about the degree to which PG affects the size and shape of C. trachomatis during its division process, and recent studies suggest the process is initiated via a polarized mechanism. We conducted an imaging study to ascertain the dimensions, orientation, and relative density of chlamydial PG throughout the organism’s developmental cycle. Our analysis indicates that PG in replicating C. trachomatis can be associated with four, broad structural forms; polar/septal disks, small/thick rings, large rings, and small/thin rings. We found that PG density appeared to be highest in septal disks and small/thick rings, indicating that these structures likely have high PG synthesis-to-degradation ratios. We also discovered that as C. trachomatis progresses through its developmental cycle PG structures, on average, decrease in total volume, indicating that the average cell volume of chlamydial RBs likely decreases over time. When cells infected with C. trachomatis are treated with inhibitors of critical components of the microbe’s two distinct PG synthases, we observed drastic differences in the ratio of PG synthesis to degradation, as well as the volume and shape of PG-containing structures. Overall, our results suggest that C. trachomatis PG synthases differentially regulate the expansion and contraction of the PG ring during both the expansion and constriction of the microbe’s cell membrane during cell growth and division, respectively.